How Much is the Amazon Worth? The State of Knowledge Concerning the Value of Preserving Amazon Rainforests - May, Peter H.; Silveira Soares-Filho, Soares-Filho; Strand, Jon (World Bank, Washington, DC, 2014)
This paper surveys the current state of knowledge concerning the value of the Amazon rainforest, including a survey of work to date to quantify changes in economic values when the rainforest cover changes. The focus is on local and regional impacts of forest loss or protection, including both gross values of forest protection and opportunity costs of converting the forest to other uses including agriculture. Important gross value items surveyed are timber and non-timber product extraction from a sustainably maintained rainforest; local values of eco-tourism; biological resources including bio-prospecting; a range of hydrological impacts including watershed protection, hydropower production, and changes in rainfall patterns; and impacts of forest fires and their control. Mapping such values in geographical space is of high value for implementing efficient and effective (Reducing Emissions from Deforestation and Forest Degradation ) programs for protecting the remaining forest. The current data basis for such mapping is found to be quite weak and in need of improvement for all value elements.